Cardiovascular disease and preventive care service utilization among midlife adults: The roles of diagnosis and depression - Kang Sun; Min Zhan (Elsevier, 2024)
Objectives: Secondary preventive care is important for monitoring the progression of cardiovascular disease (CVD). However, the factors that promote secondary prevention were not well understood. This study addressed this gap by investigating the impact of CVD diagnosis on preventive care utilization among midlife adults. Given the high prevalence of depression among this population, it further examined whether depression interacted with CVD diagnosis to affect preventive care utilization. Methods: The study sample included 6,222 midlife adults from six waves of the National Longitudinal Survey of Youth 1979 (NLSY79) collected between 2006 and 2016. Multiple logistic regressions were conducted to examine the relationship between a CVD diagnosis and each of the five types of preventive care utilization: influenza vaccinations, electrocardiography (EKG) and screening for high blood pressure, cholesterol, and blood sugar. Depression was then added to examine its possible moderation effect. Results: The results showed that midlife adults with a CVD diagnosis were more likely to utilize all five types of preventive care services. EKG, the most relevant preventive care type with CVD diagnosis, had the largest strength of likelihood. Depression strengthened the relationship between a CVD diagnosis and the utilization of blood pressure tests, but it showed no associations with other four types of preventive care utilization. Conclusions: The study findings indicate that a CVD diagnosis could serve as an opportunity for promoting secondary preventive care utilization. Future research needs to explore how a CVD diagnosis affects different population groups, and further explore the roles of depression.